Vētanta cittānta Vīracaiva camayācāriyārākiya Tuṟaimaṅkalam Civappirakācacuvāmikaḷ aruḷicceyta Pirapuliṅkalīlai - Civappirakācar, 17th cent (SAMP early 20th-century Indian books project, 1930)
Epic poem on Allamaprabhu, fl. 1160, Lingayat saint; edited with commentary.